Tacit Working Models of Human Behavioural Change Ii: Farmers’ Folk Theories of Conservation Programme Design - Zorondo-Rodriguez, F (Springer, 2020)
Community involvement may be essential for conservation programme success. We focus on farmers, asking how and why they believe conservation interventions will work, or not. Here we test models of folk theories of the human motivational factors required for behaviour change, in 3 rural central Chilean communities. We hypothesize that different models will be supported by farmers with different experiences with conservation programmes, and that socioeconomic and production system variation will explain further variation in who supports each working model. We use a multiple methods approach, combining a questionnaire with participant-observation. We find support for three of the working models of human behavioural change, among different socio-economic profiles of farmers. We believe that the schema of working models provides a boundary object to facilitate communication between conservationists and stakeholders, and can help improve conservation project design and implementation. © 2020, Royal Swedish Academy of Sciences.